Hypobarotherapy and cardiovascular risk factor correction in women in early postmenopause - S. K. Kshnyaseva; O. D. Konstantinova; A. N. Tin’kov (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To assess the role of hypobarotherapy in the correction of cardiovascular disease (CVD) risk factors (RF) among women in early postmenopause. Material and methods. The hypobaric hypoxia adaptation method (Ural-1 barochamber, 22 daily three-hour sessions; simulated altitude 3500 m, or 460 mm Hg) was used for the metabolic syndrome treatment in 56 women (mean age 53,6±3,1 years) in early postmenopause. Results. The treatment-induced decrease reached 53,5% for modified menopausal index; 6,1% for body mass; 13,4% and 7,3% for systolic and diastolic blood pressure; 19,5% for cholesterol; 21,3% for glucose; and 20,2% for insulin. Systolic and diastolic left ventricular function parameters also improved. Conclusion. Hypobarotherapy was an effective method for the CVD RF correction among women in early postmenopause.